The Baltic Republics and the First Symptoms of the USSR’s Dissolution - David Ramiro Troitiño (Pasado y Memoria)
Despite the tough repression suffered by the local population of the Baltic Republics and the relative social peace after the death of Stalin, Estonia, Latvia and Lithuania maintained a differential consciousness with the rest of the Soviet Union. Parallel, the Soviet inability to maintain a coherent and sustainable socio-economic system opened deep cracks in in the society due a search of reforms to sustain the system. This historical moment was used by the Baltic Soviet Republics to aim for their own alternative society model. Understanding this correlation between the Soviet Union crisis and the differential path chosen by the Baltics is crucial in this publication following its main target of understanding the occupation of the Baltic States and the circumstances around the Baltic Way that united the three Republics in a unique movement of peaceful demonstration leading to their independence. The analysis employs a historical-interpretative method, emphasizing the interrelation between political, economic, and cultural resistance patterns.